Evaluation of safety and efficacy of intracranial self-expanding drug-eluting stents for symptomatic intracranial atherosclerotic stenosis: a prospective, multicentre, randomised controlled, superiority clinical trial protocol - Yang Zhao; Yingkun He; Liangfu Zhu; Ziliang Wang; Wenbo Liu; Yanyan He; Zhengpeng Zhu; Jingge Zhao; Qianhao Ding; Shikai Li; Yukuan Pang (BMJ Open)
Background In-stent restenosis (ISR) is a crucial factor that affects the long-term efficacy of intracranial bare metal stent (BMS) implantation for intracranial atherosclerotic stenosis (ICAS). Patients with intracranial ISR are at a high risk of recurrent ischaemic events. The NOVA intracranial drug-eluting stent (DES) trial demonstrates that a DES can reduce ISR and stroke recurrence after intracranial bare stent implantation. However, the application of balloon-expanded DES necessitates specific vascular conditions. The objective of this study is to assess the safety and efficacy of self-expanding DES for treating symptomatic ICAS (sICAS).Methods This is a prospective, multicentre, randomised, controlled, superiority clinical trial that is conducted in 16 clinical trial centres in China. This study aims to recruit 208 patients with sICAS. Eligible subjects are randomly assigned to two groups at a ratio of 1:1. The experimental group is treated with DES (Xinwei intracranial DES system). The control group is treated with BMS (Wingspan intracranial stent system). All subjects are followed up within 7 days after surgery or before discharge; 30 days after surgery; and 6, 12 and 24 months after surgery. The primary outcome of the trial is the incidence of ISR at 6 months after surgery to verify the safety and efficacy of intracranial DESs. After 6 months of follow-up, the clinical summary report is issued for product registration application, and the follow-up of 12 months and 24 months after operation is conducted to evaluate the medium and long-term efficacy.Ethics and dissemination The study involving human participants is reviewed and approved by the Ethics Committee of Drugs (devices) Clinical Experiment in Henan Provincial People’s Hospital (reference number: AF/SC-08/05.0) and other research centres participating in the clinical trial (supplemental file 2). The results yield from this study will be presented at international conferences and sent to a peer-reviewed journal to be considered for publication.Trial registration number Registered on 2 November 2023 with Chinese clinical trial registry. Registration number is ChiCTR2300077271.